73 Importance of classification and reassessment in patients with pah-chd: the norpap database. (5th June 2017) - Abraham, Dilip; Bingham, Ruth; Ranu, Ranu; Head, Catherine; Lewis, Clive; Freeman, Leisa J
Abstract : Background: Patients with Pulmonary Arterial Hypertension associated with Congenital Heart Disease (PAH-CHD) are subdivided into 4 categories: 1) Eisenmenger Syndrome, 2) PAH with systemic-to-pulmonary shunts, 3) PAH with coincidental defects, 4) PAH after defect correction. There is clear benefit for targeted therapy in Category 1, 2 (less so in those with segmental PAH), and 4. Methodology: The NORPAP database was created in 1993 and contains 2854 patients. Patients in Norwich and Papworth have access to the joint GUCH-PVDU (Grown Up Congenital Heart Disease – Pulmonary Vascular Disease Unit) service. Patients with PAH-CHD were extracted from the NORPAP database and the above classification system applied. Results: 98/2854 (3.4%) of patients had PAH-CHD. Female:male ratio 1.65:1. Age range 18–96, mean age 47, median 43.5. Trisomy 21 in 40 patients. Underlying condition shown in Figure 1. Number of patients per Category is as follows (Figure 2): Category 1 (71/98=72%, Age Range=25–92, median 42), Category 2 (18/98=18%, Range 18–96, median 58), Category 3 (3/98=3%, Range 38–90, Median 42), Category 4 (6/98=6%, Range 24–69 Median 45: diagnoses – DORV, VSD, TGA (atrial switch), PDA, PA-VSD, secundum ASD). 2 patients in category 4 had mixed aetiology with Chronic Thromboembolic Pulmonary Hypertension (CTEPH). 26/98 (27%) of patients have died. Median age at death 41. Category 1: 21/71 29.5%, Category 2: 2/18=11%, Category 3: 1/3=33%, Category 4: 2/6=33%. 55/98 (56%) are on targeted therapy. In the Eisenmenger group 41/71 (58%) are on targeted therapy. Sildenafil 11/41=26.8%, Bosentan 13/41=31.7%, Ambrisentan 1/41=2.4%, two agent therapy 16/41=39%. Pre-treatment 6 min walk mean 288.5m, post-treatment mean 320.6m. Paired two sample t-test analysis reveals a significant difference in 6 min walk test (t-stat 2.02, p 0.01). Of note was 28 year old Patient X: Trisomy 21 with large VSD and subpulmonary stenosis and suggestion of double outlet RV on poor quality echocardiography. Reassessed with cardiac MRI which confirmed tetralogy of Fallot. Following RHC, which showed RVOT gradient of 18 mmHg, mean PA pressure 55, PVR 25 wood units falling to 15.8 with maximal pulmonary vasodilatation, he was started on sildenafil. Conclusion: Targeted therapy in PAH-CHD improves quality of life, delays time to deterioration and may have a mortality benefit.Our limited data supports the evidence that targeted therapy improves objective exercise tolerance. Adult follow up surveillance clinics must be alert to deterioration of functional class in Category 1; Trisomy 21 patients that have been labelled as PAH, but may have normal PA pressure at right heart catheterisation; high index of suspicion with new symptoms in repaired CHD who develop PAH (Category 4). Although Patient Xs management did not change, we highlight the case to remind clinicians of need to always reassess patients with historical and sometimes inaccurate labels.